POLA ASUH, MAKAN DAN SANITASI PADA KEJADIAN STUNTING DI DESA REBALAS WILAYAH PUSKESMAS GRATI KABUPATEN PASURUAN - Olivia Vebi Safitri; Dwi Helynarti Syurandhari; Agustin Dwi Syalfina (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Stunting is a chronic nutritional problem. In the future they will experience difficulties in achieving optimal physical and cognitive development. Stunting is influenced by food availability, parenting style, and environmental sanitation. The purpose of this study was to determine the effect of parenting, eating patterns, and sanitation patterns on stunting in Rebalas Village, Grati Health Center Region, Pasuruan Regency. This research was case-control. Population was grouped between stunted and normal under-five children with a sample of 47 respondents and a ratio of 1:1, sample was taken by purposive sampling. The independent variables were parenting, eating patterns, and sanitation patterns, while the dependent variable was the incidence of stunting. The data that has been collected then processed through editing, coding, scoring, and data tabulation. Then analyzed using the Chi-Square test Based on the results of the study, it was found that respondents with parenting, eating patterns, and sanitation patterns in the unfavorable category for their children, almost half had stunted children. Chi-Square test obtained a probability value = 0.0000 <0.05 so that H1 was accepted, which mean that there was an influence of parenting patterns, eating patterns, and sanitation patterns. Under-five children with normal height (not stunted) have better parenting patterns, eating patterns, and sanitation patterns than stunted children with the same family economic background. Improving nutritional problems by empowering the community as preventive and promotive efforts to change family habits and recognizing the positive habits of under-five children mothers and being able to spread these positive habits to other mothers